TWO-DIMENSIONAL GEOMETRIC OPTIMIZATION OF AN OSCILLATING WATER COLUMN CONVERTER IN LABORATORY SCALE - Gomes, M. N.; Nascimento, C. D.; Bonafini, B. L.; Santos, E. D.; Isoldi, L. A.; Rocha, L. A. O. (Revista de Engenharia Térmica, 2012)
The present paper presents a two-dimensional numerical study about the geometric optimization of an ocean Wave Energy Converter (WEC) into electrical energy that has as operational principal the Oscillating Water Column (OWC). To do so, the Constructal Design fundamentals were employed to vary the degree of freedom H1/L (ratio between height and length of the OWC chamber), while the other degree of freedom H2/l (ration between height and length of chimney) was kept constant. The OWC chamber area (φ1) and the total OWC area (φ2) are also kept fixed, being the problem constraints. In this study was adopted a regular wave with laboratory scale dimensions. The main goal was to optimize the device’s geometry aiming to maximize the absorbed power when it is subjected to a defined wave climate. For the numerical solution it was used the Computational Fluid Dynamic (CFD) commercial code FLUENT®, which is based on the Finite Volume Method (FVM). The multiphasic Volume of Fluid (VOF) model was applied to treat the water-air interaction. The computational domain was represented by an OWC device coupled into a wave tank. Thereby, it was possible to analyze the WEC subjected to regular wave incidence. An optimal geometry was obtained for (H1/L)o=0.84, being this one approximately ten times more efficient then the worst case (H1/L = 0.14), showing the applicability of Constructal Design in this kind of engineering problem.